Tinjauan Yuridis Penerapan Sanksi Pidana Bagi Pelaku Perdagangan Flora dan Fauna yang Dilindungi - Siregar, M Yusuf Habibi; Munthe, Riswan (Universitas Medan Area, 2025)
The application of criminal sanctions for violations of Law No. 32 of 2024 on the Conservation of Natural Resources and Their Ecosystems has a strategic role in protecting biological wealth in Indonesia, including in North Sumatra. This thesis examines the legal aspects related to the application of criminal sanctions for violators of the law, by highlighting the obstacles, effectiveness, and implications for conservation efforts in this region. This study found that although regulations have been in place, their legal implementation still faces various challenges such as lack of supervision, less than optimal law enforcement, and low levels of public awareness. This situation has an impact on the success of natural resource conservation efforts in North Sumatra. The results of this study emphasize the importance of collaboration between various parties, legal harmonization, and increasing public education to create an effective and sustainable conservation system.